Cooking the Singapore identity through the palate. - Lim, Pei Ling. (2011)
This research studies how Singapore identity is created and reflected in food. Food is also utilised by the Singapore state in defining the discourse of multiculturalism in the city-state. A qualitative approach was utilized in this research. An ethnographic study was carried out in three hawker centres in Singapore. A survey was also conducted with Singaporeans based overseas. Finally, a contextual analysis on “Overseas Singapore Day” was carried out. This event is organised by the Prime Minister’s Office (PMO) annually. My findings show that food is a form of cultural hybridity in Singapore, and it opposes to how the state defines the Singapore identity in its discourse.